Immunomodulation by IVIg and the Role of Fc-Gamma Receptors: Classic Mechanisms of Action after all? - Nagelkerke, Sietse Q.; Kuijpers, Taco W. (Frontiers in Immunology, 2015)
Intravenous IgG (IVIg) contains polyclonal IgG from thousands of donors. It is administered at a low dose at regular intervals as antibody replacement therapy and at a higher dose as immunomodulatory treatment in various auto-immune or auto-inflammatory diseases. The working mechanism of immunomodulation is not well understood. Many different explanations have been given. During the last decade we have focused on classical antibody binding via the Fc-domain of the IgG molecules to the common IgG receptors, i.e. the Fcγ receptors (FcγRs). Variation in the genes encoding human FcγRs determines function as well as expression among immune cells. As described here, NK cells and myeloid cells, including macrophages, can express different FcγR variants, depending on the individual’s genotype, copy number variation (CNV) and promoter polymorphisms. B cells seem to only express the single inhibitory receptor. Although these inhibitory FcγRIIb receptors are also expressed by monocytes, macrophages, and only rarely by NK cells or neutrophils, their presence is unlikely to explain the immunomodulatory capacity of IVIg, nor does the sialylation of IgG. Direct IVIg effects at the level of the activating FcγRs, including the more recently described FcγRIIc, deserve renewed attention to describe IVIg-related immunomodulation.